The Polymerization of Homogentisic Acid In Vitro as a Model for Pyomelanin Formation. Issue 6 (10th February 2022) - Galeb, Hanaa A.; Lamantia, Angelo; Robson, Alexander; König, Katja; Eichhorn, Jonas; Baldock, Sara J.; Ashton, Mark D.; Baum, John V.; Mort, Richard L.; Robinson, Benjamin J.; Schacher, Felix H.; Chechik, Victor; et al.
Abstract: Melanins are a class of biopolymers that are widespread in nature, with diverse origins, compositions, and functions, and their chemical and optoelectronic properties render them potentially useful for application in materials science for various biotechnological applications. For patients with alkaptonuria, the accumulation of homogentisic acid (HGA) in their bodies is associated with the concomitant deposition of pyomelanin, which is a pigment that contains significant amounts of polymerized HGA (polyHGA) in the bodily tissues of the patients. The polymerization of HGA under various different conditions in vitro is investigated using a selection of different analytical chemistry techniques to understand if there may be a correlation between the conditions and pigment deposition in vivo, and their potential for application as green/sustainable and components of electronic devices. Abstract : Homogentisic acid (HGA) polymerization to form polyHGA (a simplified version of pyomelanin) is investigated in the absence/presence of enzymes at physiologically relevant pH values. Their chemical, paramagnetic, and electrical properties are analyzed to assess if there may be a correlation between the conditions and pigment deposition in vivo and their prospects for use as sustainable resources for advanced biotechnological applications.